DAMPAK PENGEMBANGAN KOMODITAS KELAPA DALAM TERHADAP PEREKONOMIAN PROVINSI JAMBI - Rizki Gemala Busyra (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Jambi is one of the central of estate crop productions in Indonesia. In 2006, the Minister of Agriculture issued the Regulation about Revitalization Program. Revitalization Program is an effort to accelerate the development of smallholders through expansion, renovation and rehabilitation of tree crops. Along with minister of agriculture policy, the Jambi province activities focused on the development commodity coconut. The purpose of this study is to identify the factors that affect the area, production, productivity, commodity prices and export in the Jambi province, and to analyze the impact of development of coconut on the economy of Jambi province. This study uses secondary data is structured as pooled annual data on nine districts in Jambi province, starting 2000 until 2009. The result of this study shows the expansion of coconut can improve the economy of Jambi.Keywords: Econometric Model, Coconut, Jambi Province